(untitled) (Research, Society and Development, 2021)
The present study aimed to assess Ecoefficiency (EE) related to the emission of Greenhouse Gases (GHG) from the transport of the inputs used to provide complementary meals at a large university hospital in Brazil. For EE calculations, the annual energy supply in kilocalories of the inputs used and the estimated GHG emissions were considered, considering the distance in kilometers between the place of origin of each product and the destination city in southern Brazil. 31 products were used and selected for complementary meals distributed in the groups of: dairy products, cookies, drinks, supplements, and enteral diets for adults and pediatrics. The results showed that EE was directly related to the origin of the products, especially in enteral diets. The application of the Spearman correlation coefficient showed a strong negative correlation of -0.8119 [CI (95%) -0.9023; -0.6531] between the variables distance in kilometers and eco-efficiency and also when comparing GHG emissions with kilocalories. The health sector must play its role in relation to environmental impacts also in the assessment of GHG emissions in the context of nutritional therapy.